KOMUNIKASI PENYULUHAN SATUAN BINA MASYARAKAT (SATBINMAS) POLRESTA PEKANBARU DALAM MENGANTISIPASI KENAKALAN REMAJA DI KALANGAN SISWA TINGKAT SMP KOTA PEKANBARU - ", Stefani; Awza, Rusmadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
School periods are very vulnerable and need to be monitored and given counseling about the dangers of juvenile delinquency, namely the process of beginning the teenager itself, namely when stepping on junior high school (SMP). The need for counseling and understanding of the dangers of promiscuity, drugs and other delinquency should be instilled during junior high school. The researcher was interested in knowing the counseling communication held by the Community Development Unit (Satbinmas) Pekanbaru Police carried out coaching and counseling activities on juvenile delinquency at the junior high school level in Pekanbaru City. The purpose of this counseling is to find out the selection of communicators on counseling, counseling messages, counseling media, target counseling and the effects of counselingThe research method used in this study is a qualitative research method. This qualitative research aims to explain the phenomenon as deeply as possible through the deep collection of data. Using a purposive technique with interview data collection techniques, observation, documentation, using data analysis techniques, and using data validation techniques to extend participation and triangulation.The source of counseling in this study is the SatBinmas Polresta Pekanbaru, usually the communicator of this counseling, is Aiptu Siregar. Counseling is usually held in schools in the city of Pekanbaru with a time that has been adjusted by the school. Message in counseling held by Sat Binmas Polresta Pekanbaru in Anticipating Juvenile Delinquency is informative and persuasive. In conducting counseling through media seminars presentation is assisted with powerpoint slide media through infocus. Participants or recipients of the Sat Binmas Polresta Pekanbaru counseling about anticipation of juvenile delinquency are school students, parents, and the community. The expected feedback from the counseling on juvenile delinquency anticipation carried out by Sat Binmas Polresta Pekanbaru is the declining percentage of juveniles in Pekanbaru City.